(untitled) - Trần, Thị Quế Nhi (Cần Thơ, 2018)
This thesis introduce about high school students' perceptions of the use of facebook-based e-portfolios in writing.
Keywords: English language,Tiếng Anh; Study and teaching,Học và dạy học